Высокотемпературное испарение капель воды с твердыми нерастворимыми примесями - Шахрай М. С. Михаил Сергеевич; Антонов Д. В. Дмитрий Владимирович; Стрижак П. А. Павел Александрович; Сажин С. С. Сергей Степанович (2025, 2025)
Заглавие с экрана